Human decidua basalis mesenchymal stem/stromal cells enhance anticancer properties of human natural killer cells, in vitro - Almutairi, Abdulaziz; Alshehri, Najlaa A.; Al Subayyil, Abdullah; Bahattab, Eman; Alshabibi, Manal; Abomaray, Fawaz; Basmaeil, Yasser S.; Khatlani, Tanvir (Frontiers in Cell and Developmental Biology, 2024)
IntroductionMesenchymal stem cells/stromal cells from the Decidua Basalis of the human placenta (DBMSCs) express wide range of effector molecules that modulate the functions of their target cells. These properties make them potential candidate for use in cellular therapy. In this study, we have investigated the consequences of interaction between DBMSCs and natural killer (NK) cells for both cell types.MethodsDBMSCs were cultured with IL-2-activated and resting non-activated NK cells isolated from healthy human peripheral blood and various functional assays were performed including, NK cell proliferation and cytolytic activities. Flow cytometry and microscopic studies were performed to examine the expression of NK cell receptors that mediate these cytolytic activities against DBMSCs. Moreover, the mechanism underlying these effects was also investigated.ResultsOur findings revealed that, co-culture of DBMSCs and NK cells resulted in inhibition of proliferation of resting NK cells, while proliferation of IL-2 activated NK cells was increased. Contrarily, treatment of DBMSC’s with comparatively high numbers of IL-2 activated NK cells, resulted in their lysis, whereas treatment with low numbers resulted in reduction in their proliferation. Cytolytic activity of NK cells against DBMSCs was mediated by several activating NK cell receptors. In spite of the expression of HLA class I molecules by DBMSCs, they were still lysed by NK cells, excluding their involvement in cytolytic activity. In addition, preconditioning NK cells by DBMSCs, enhanced their ability to suppress tumor cell proliferation and in severe cases resulted in their partial lysis. Lysis and decrease of tumor cell proliferation is associated with increased expression of important molecules involved in anticancer activities.DiscussionWe conclude that DBMSCs exhibit dualfunctions on NK cells that enhance their anticancer therapeutic potential.